A Literature Review on the Role of Blockchain Technology in Enhancing Information System Security - Jusmawati; Tomi Apra santosa (Indonesia Journal of Engineering and Education Technology (IJEET), 2025)
This study aims to examine the role of blockchain technology in enhancing information system security. With increasing reliance on digital platforms, maintaining data integrity, confidentiality, and availability has become a major challenge. Blockchain, as a decentralized and immutable ledger system, offers a solution by providing transparency, audit trails, and resistance to manipulation. This study systematically analyzes recent research articles, case studies, and theoretical frameworks to evaluate how blockchain mechanisms such as cryptographic hashes, consensus protocols, and smart contracts contribute to strengthening information system security. The results demonstrate blockchain's potential in addressing vulnerabilities related to data leakage, fraud, and unauthorized access in various sectors, including finance, healthcare, and supply chain management. However, challenges such as scalability, regulatory compliance, and integration complexity are also critically discussed. This study aims to provide a comprehensive understanding of blockchain's capabilities and limitations in securing information systems and provide insights for future research and practical implementation.